Analisis Pendapatan Berdasarkan PSAK No. 23 Pada PDAM Tirta Wampu Stabat - Putri Kemala Dewi Lubis (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2018)
This study aims to analyze the accounting behavior of income based on statement of financial accounting standards number 23 and to find out whether the accounting treatment of income of PDAM Tirta Wampu Stabat is in accordance with statement of financial accounting standards number 23. The research approach used in this study is a descriptive case study by describing the actual circumstances and properties of the object of research. The results of the research conducted, it is known that PDAM Tirta Wampu Stabat has implemented adequate accounting procedures in terms of participation and has implemented a policy of recognizing, recording, measuring, disclosing and reporting income in accordance with the statement of financial accounting standards number 23 (statement of financial accounting standards number 23) concerning income. However, for recognition of fines and recognition of new connections not in accordance with statement of financial accounting standards number 23. This occurs because revenue from new fines is recognized when cash is received while new connection revenues at the end of the year are recognized as income in the current period, even though new connection services are provided in the future period. Penal income should be recognized when one day after the due date. New connection revenues should be recognized as revenue in the future period because based on statement of financial accounting standards number 23, income must be recognized in the accounting period when the service is rendered.